2021
DOI: 10.1111/scd.12617
|View full text |Cite
|
Sign up to set email alerts
|

Caries experience in caregiver‐intellectual deficient pair: Influence of caregiver's psychological morbidity

Abstract: Objective: Evaluate how determinants of psychological morbidity were associated with dental caries experience in the caregiver-intellectual deficient pair. Methods: A cross-sectional study with 299 pair, who had their oral health status assessed using the DMFT index (decayed, missing and filled teeth). Symptoms of anxiety, depression, stress, quality of sleep, and socioeconomic variables were measured in caregivers. Adjusted prevalence ratios were estimated using Poisson regression with the caregiver and child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…A recent study reported that symptoms of depression, anxiety and stress were associated with higher levels of dental caries experience for caregivers of people with intellectual disabilities 6 . With regard to dental caries experience, the present study showed similar results for the two groups of caregivers.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…A recent study reported that symptoms of depression, anxiety and stress were associated with higher levels of dental caries experience for caregivers of people with intellectual disabilities 6 . With regard to dental caries experience, the present study showed similar results for the two groups of caregivers.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, when evaluating oral health conditions, parental caregivers of children with DS had a higher rate of gingival bleeding compared to controls. This observation suggests that oral health care may be deficient in these caregivers, in agreement with previous studies that have indicated that caregivers of individuals with intellectual disabilities have little time for themselves and their own care 6,26 . Caregivers often neglect their own health in favor of prioritizing the person being cared for, leading to the deterioration of their health and quality of life 5,6,27 …”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations